Strategies to Reduce CO2 Emissions in Housing Building by Means of CDW - Ulises Mercado Burciaga; Paola Villoria Sáez; Francisco Javier Hernández Ayón (Ital Publication, 2019)
One of the biggest problems that human beings face is climate change and construction industry is one of the sectors causing the greatest impact, which has led him to adopt sustainable strategies. However, these have not been effective enough to reduce CO2 emissions, since solutions are required accompanied by other alternatives. Therefore, the objective of this study is to reduce CO2 by implementing CDW strategies under the following method: 1) analysis of CO2 of the major raw materials consumed, 2) use of the materials at the construction site was determined, 3) waste streams generated at the construction site were identified and those that could be reuse were highlighted, 4) CDW recycling strategies to avoid the use of the major raw materials consumption are proposed, and 5) one of the strategies proposed is further analyzed. The results show that natural aggregates generate the greater amount of CO2 due to the consumption of fuel required for their transportation. By replacing 68% of natural aggregates by recycled aggregates, CO2 can be reduced by 53%. Finally, these results can help to promote the opening of new CDW recycling companies in Nayarit and thereby contribute to the sum of sustainability practices in housing building.